Оценка точности упрощенного динамического расчета систем с распределенными параметрами на примере однопролетной жестко защемленной балки с консолью - Шевченко, Ф. Л.; Царенко, С. Н. (Видавництво Львівської політехніки, 2011)
Розглядається спрощений динамічний розрахунок однопрольотних балок з консолею, оснований на заміщенні заданої системи з розподіленими параметрами невагомою балкою з одною масою за умовою рівності частоти основного тону коливань і частоти еквівалентної балки. There are many methods of the approached dynamic calculation of systems with the distributed parametres the most part from which is based on replacement of the valid elastic system with the distributed parametres the simplified system with one degree of freedom on the basis of equality of their frequencies. The purpose of present article is distribution of it before the offered simplified method on single-slope beams with the console, if information about the exact calculation of spectrum of eigenfrequencies not led in referenced literature.